SIMPLE ACCOUNTING TRAINING FOR MSMES GARMENT ENTREPRENEURS TO IMPROVE BUSINESS PERFORMANCE - Laksono, R. Rosaleh; Dewabrata, Ignatius Oki; Gunanta, Remon; Indah, Bunga (CENTRAL ASIA AND THE CAUCASUS, 2022)
Small and medium enterprises (MSMEs) have a major role for economic growth and development in Indonesia. One of the problems of the low competitiveness of traditional business actors (MSMEs) is the limited ability of business actors to manage the finances of business organizations. This study aims to provide basic accounting knowledge in helping the economy of micro, small and medium enterprises (MSMEs). The research was conducted on the garment home industry located in Cikadut, Mandalajati sub- district, Bandung city, West Java province. The target of this training is to deliver a concept and framework for how to later organize or develop an Organization or Business Unit with Financial Reports as basic knowledge or fundamentals in decision-making. In the Basic Accounting Training, it is expected to be able to understand the basic concepts of accounting well. There are three main materials about the basic concepts of accounting that must be mastered in the Basic Accounting Training, namely the understanding of assets, liabilities, and equity. From the three materials, it is hoped that knowledge of assets, liabilities, and equity will make it easier to understand all the problems that will be encountered in accounting. Basic Accounting Training will provide an important foundation and have a great influence on their success in making good decisions with good financial information.